The Adventures of Huckleberry Finn - Twain, Mark (London Harpers Collins Publishers, 2013)
Following the events of The Adventures of Tom Sawyer, Huckleberry Finn is under the watchful stewardship of the Widow Douglas. However, when he is forced back into his drunken father's custody, Huck fakes his own death and runs off down river. In the process, he meets up with Jim, a runaway slave, and the two become friends as well as travel companions. Their adventures lead them through many twists and turns through the American South, embarking on a legendary journey.
Keywords: Mississippi River -- Boys -- Male friendship